Sequential treatment for landfill leachate by applying coagulation-adsorption process. Issue 1 (2nd January 2017) - Bashir, Mohammed J. K.; Xian, Tay Ming; Shehzad, Areeb; Sethupahi, Sumathi; Choon Aun, Ng; Abu Amr, Salem
Abstract: Landfill leachate has always been the most problematic factor in municipal solid waste management. Leachate generated from landfills generally contains high amount of organic and inorganic compounds that might cause pollution to water resources. In the current study, sequential treatment of landfill leachate using coagulation–flocculations a pretreatment process followed by adsorption process was used to treat chemical oxygen demand (COD), ammonical nitrogen (NH3 -N) and color from raw landfill leachate. Coagulation–flocculation process was examined using alum and ferric chloride. The optimum working pH for the tested coagulants was 5 and FeCl3 showed higher removal efficiency for landfill leachate than alum. The pretreated leachate was further treated via two types of adsorbents i.e., powdered activated carbon (PAC) and zeolite. The optimum experimental conditions for PAC and zeolite adsorptions were found to be 40 g/L at 30 min and 80 g/L at 120 min, respectively. Scanning electron microscope and Fourier transform infrared spectroscopy tests were conducted to examine the surface morphology and chemical properties of the adsorbents. The results showed that the Freundlich isotherm was best fitted for PAC adsorption while Langmuir isotherm model showed good conformity for zeolite adsorption. Besides, pseudo-second order model was found to be the best fitted kinetic model for both PAC and zeolite adsorption where the R 2 was closed to unity for all parameters. On balance, FeCl3 coagulation-PAC adsorption has shown higher removal efficiency for color, COD, and NH3 -N as compared to FeCl3 coagulation-zeolite adsorption.